Moderating Effects of Generation Y’s Online-to-Offline E-Commerce (O2O E-Commerce) Shopping Experience - Saribut, Salitta (Indian Journal of Marketing, 2022)
This research aimed to study the moderating effects of Generation Y’s online-to-offline e-commerce (O2O e-commerce) shopping experience. The data were collected utilizing an online questionnaire. The sample included 349 customers aged between 18 – 38 years. Descriptive statistics were used to present the percentage, mean, and standard deviation. Inferential statistics were applied by structural equation modeling (SEM) to test the moderating effects of the O2O e-commerce shopping experience as a categorical variable. Also, to compare the chi-square differences, multi-group analysis was applied. The research results revealed that online and offline data integration variables positively influenced perceived usefulness and easy-to-use. Perceived usefulness and perceived easy-to-use positively influenced customers’ attitudes towards the use of O2O e-commerce. Moreover, Generation Y’s O2O e-commerce shopping experience influenced the relationship between online and offline data integration and perceived usefulness. Furthermore, perceived easy-to-use influenced the relationship between perceived usefulness, perceived easy-to-use, and attitudes towards the use of O2O e-commerce. The results of this research can be used as a guideline for various educational institutions in helping local communities generate sustainable income, which is a very important foundation for country development. The educational institutions can act as intermediaries in purchasing products produced by local communities and distributing them through the O2O e-commerce platform created to reach the right customers, such as Generation Y.